Asksia AI LOGO

Sia

austin43400's Question
Math
Posted 8 months ago
The right solution is x - ln|e^x + 1| + 1/(e^x + 1) + C

1(ex+1)2dx\int \frac{1}{\left(e^{x}+1\right)^{2}} d x
Sign in to unlock the answer
Answer from Sia
Posted 8 months ago
Solution by Steps
step 1
We start with the integral 1(ex+1)2dx\int \frac{1}{(e^x + 1)^2} \, dx
step 2
To solve this integral, we use the substitution u=ex+1u = e^x + 1. Then, du=exdxdu = e^x \, dx and dx=duexdx = \frac{du}{e^x}
step 3
Since ex=u1e^x = u - 1, we have dx=duu1dx = \frac{du}{u - 1}. Substituting these into the integral, we get: 1u2duu1=duu2(u1).\int \frac{1}{u^2} \cdot \frac{du}{u - 1} = \int \frac{du}{u^2 (u - 1)}.
step 4
We can decompose the integrand using partial fractions: 1u2(u1)=Au+Bu2+Cu1.\frac{1}{u^2 (u - 1)} = \frac{A}{u} + \frac{B}{u^2} + \frac{C}{u - 1}.
step 5
Solving for AA, BB, and CC, we get: 1=Au(u1)+B(u1)+Cu2.1 = A u (u - 1) + B (u - 1) + C u^2.
step 6
By comparing coefficients, we find: A=1,B=1,C=0.A = 1, \quad B = -1, \quad C = 0.
step 7
Substituting back, we have: (1u1u2)du.\int \left( \frac{1}{u} - \frac{1}{u^2} \right) \, du.
step 8
Integrating term by term, we get: 1udu1u2du=lnu+1u+C.\int \frac{1}{u} \, du - \int \frac{1}{u^2} \, du = \ln|u| + \frac{1}{u} + C.
step 9
Substituting back u=ex+1u = e^x + 1, we get: lnex+1+1ex+1+C.\ln|e^x + 1| + \frac{1}{e^x + 1} + C.
Answer
lnex+1+1ex+1+C\ln|e^x + 1| + \frac{1}{e^x + 1} + C
Key Concept
Substitution and Partial Fractions
Explanation
We used substitution to simplify the integral and then applied partial fractions to decompose the integrand, making it easier to integrate term by term.

Not the question you are looking for? Ask here!

Enter question by text

Enter question by image

Unlock Smarter Learning with AskSia Super!

Join Super, our all-in-one AI solution that can greatly improve your learning efficiency.

30% higher accuracy than GPT-4o
Entire learning journey support
The most student-friendly features
Study Other Question